The Application of Emergency Concept Within the MUI Fatwa on Measles Rubella Vaccine Immunization - Sanusi, Ahmad; Miftah, Ahmad Harisul; Agustiana, Ria (al-'adalah, 2020)
In contemporary religious fatwas, the term emergency (dharurat) often appears, such as health emergencies (dharurat al-shihhiyah), cultural civilization emergencies (dharurat al-tsaqafiyah), and so on, all of which are aimed at dealing with certain emergency issues that are really urgent (mulji'ah). This paper tries to analyze the MUI Fatwa Number 33 of 2018 concerning the Measles-Rubella Vaccine. According to LPPOM MUI, this vaccine contains an element that is considered haram (unlawful) in Islam. Because of this, the use of the vaccine raises the question of whether or not it is religiously permitted. After conducting a comprehensive study, MUI, through the MUI Fatwa Number 33 of 2018, stated that even though the Rubella Measles Vaccine contains haram elements, its use is permitted. This permission, as this research concludes, is based on reasons of emergency. Such because until now there has been no other vaccine that is classified as halal  (lawful) that can be used against the measles diseases. Thus, the use of the vaccine is deemed essential and urgent in the interests of the next generation of Muslims in Indonesia and the safety of the life of the wider community.